A review of current knowledge on reproductive and larval processes of deep-sea corals - Rhian G. Waller; Savannah Goode; Di Tracey; Julia Johnstone; Annie Mercier (Marine Biology, 2023)
The presence of corals living in deep waters around the globe has been documented in various publications since the late 1800s, when the first research vessels set sail on multi-year voyages. Ecological research on these species, however, only truly began some 100 years later. We now know that many species of deep-sea coral provide ecosystem services by creating complex habitat for thousands of associated species, and thus are major contributors to global marine biodiversity. Among the many vital ecological processes, reproduction provides a fundamental link between individuals and populations of these sessile organisms that enables the maintenance of current populations and provides means for expansion to new areas. While research on reproduction of deep-sea corals has increased in pace over the last 20 years, the field is still vastly understudied, with less than 4% of all known species having any aspect of reproduction reported. This knowledge gap is significant, because information on reproduction is critical to our understanding of species-specific capacity to recover from disturbances (e.g., fishing impacts, ocean warming, and seafloor mining). It is important, therefore, to examine the current state of knowledge regarding deep-sea coral reproduction to identify recent advances and potential research priorities, which was the aim of the present study. Specifically, this review synthesizes the research carried out to date on reproduction in deep-living species of corals in the orders Alcyonacea, Scleractinia, Antipatharia, Pennatulacea (class Anthozoa), and family Stylasteridae (class Hydrozoa).